1998
DOI: 10.1016/s0092-8674(00)81220-9
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of TAFIIs Are Integral Components of the SAGA Complex Required for Nucleosome Acetylation and Transcriptional Stimulation

Abstract: A number of transcriptional coactivator proteins have been identified as histone acetyltransferase (HAT) proteins, providing a direct molecular basis for the coupling of histone acetylation and transcriptional activation. The yeast Spt-Ada-Gcn5-acetyltransferase (SAGA) complex requires the coactivator protein Gcn5 for HAT activity. Identification of protein subunits by mass spectrometry and immunoblotting revealed that the TATA binding protein-associated factors (TAF(II)s) TAF(II)90, -68/61, -60, -25/23, and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
342
0
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(365 citation statements)
references
References 58 publications
16
342
0
7
Order By: Relevance
“…The SPT genes encode many proteins important in transcription, including subunits of the SAGA histone-modifying complex (Grant et al 1998), TBP itself, and histones (Clark-Adams et al 1988;Winston and Sudarsanam 1998;Yamaguchi et al 2001). SPT10 is not an essential gene, but the null allele is associated with very slow growth and defects in gene regulation (Denis and Malvar 1990;Natsoulis et al 1991;Prelich and Winston 1993;Yamashita 1993;Dollard et al 1994;Natsoulis et al 1994).…”
Section: Cell-cycle-dependent Activation Of the Histone Genesmentioning
confidence: 99%
“…The SPT genes encode many proteins important in transcription, including subunits of the SAGA histone-modifying complex (Grant et al 1998), TBP itself, and histones (Clark-Adams et al 1988;Winston and Sudarsanam 1998;Yamaguchi et al 2001). SPT10 is not an essential gene, but the null allele is associated with very slow growth and defects in gene regulation (Denis and Malvar 1990;Natsoulis et al 1991;Prelich and Winston 1993;Yamashita 1993;Dollard et al 1994;Natsoulis et al 1994).…”
Section: Cell-cycle-dependent Activation Of the Histone Genesmentioning
confidence: 99%
“…In contrast, genetic analysis of other TFIID subunits that have sequence similarities to the core histones has shown that they are required for the transcription of a larger number of genes (Apone et al, 1998;Holstege et al, 1998;Michel et al, 1998;Moqtaderi et al, 1998;Natajaran et al, 1998;Sanders et al, 1999;Reese et al, 2000). The interpretation of these results is complicated by the presence of certain TAF II s in the SAGA histone acetyltransferase complex (Grant et al, 1998), and their function in multiple complexes may partially explain the expanded requirement for these TAF II s in transcription (Lee et al, 2000). However, while Yeast Yeast 2001; 18: 1197-1205.…”
Section: Introductionmentioning
confidence: 99%
“…The yeast SAGA complex is composed of several distinct classes of factors including alteration/deficiency in activation (ADAs), suppressor of Ty (SPTs), TATAbinding protein-associated factors (TAFs), general control non-repressed 5 (GCN5) and TRA1, and acts as a transcriptional coactivator/adapter required at specific promoters (Grant et al, 1998;Hampsey, 1998). Recently, novel SAGA components such as UBP8, SGF11, SGF29, SGF73 and SUS1 have been identified (Sanders et al, 2002;Rodriguez-Navarro et al, 2004).…”
Section: Introductionmentioning
confidence: 99%